In situ nanostructure design leading to a high figure of merit in an eco-friendly stable Mg2Si0.30Sn0.70 solid solution. Issue 20 (9th February 2016) - Yin, Kang; Su, Xianli; Yan, Yonggao; Uher, Ctirad; Tang, Xinfeng
Abstract : The relationship between the temperature and the composition as well as the microstructure of a Sb-doped Mg2 Si0.30 Sn0.70 solid solution was systematically studied according to the Mg2 Si–Mg2 Sn pseudo-binary phase diagram. Abstract : The relationship between the temperature and the composition as well as the microstructure of a Sb-doped Mg2 Si0.30 Sn0.70 solid solution was systematically studied according to the Mg2 Si–Mg2 Sn pseudo-binary phase diagram. This work shows that the composition, distribution pattern, and fraction of in situ nanostructures can be controlled by the heat treatment carried out at a specific peritectic reaction temperature. A large number of in situ nanoprecipitates were observed when the sample was quenched at 900 K or 1130 K. However, quenching at 900 K resulted in the formation of agglomerates while quenching at 1130 K yielded a more even dispersion of nanoprecipitates. Monochromatic X-ray studies, back-scattering images and HRTEM results showed that the composition of the nanoprecipitates when quenched at 900 K was the Mg2 Si-rich phase, while the nanostructure was the Mg2 Sn-rich phase when quenched at 1130 K. The lattice thermal conductivity decreased dramatically due to the well distributed Mg2 Sn-rich nanoprecipitates, and the maximum ZT of about 1.2 was achieved at around 750 K. Moreover, the average value of the figure of merit ZT average reached about 0.9 in the range of 300–800 K, about a 15% higher value than in the sample composed of Mg2 Si-rich nano-agglomerates. This study demonstrates that carrying out heat treatments at the phase transformation temperatures is a simple and controllable method to design and form in situ nanostructures, which is of vital importance in the fabrication of nanocomposites and optimization of the thermoelectric performance.